2001
DOI: 10.1086/322787
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Clearance of Glucuronoxylomannan, the Major Capsular Polysaccharide ofCryptococcus neoformans:A Critical Role for Tissue Macrophages

Abstract: Cryptococcus neoformans produces a life-threatening meningitis in patients who are immunocompromised by AIDS. A striking feature of cryptococcosis in AIDS is high serum levels of the major capsular polysaccharide, glucuronoxylomannan (GXM). Soluble GXM has numerous biologic activities that may contribute to the pathogenesis of infection. The objective of the study was to further understand in vivo processing of GXM. Mice were injected intravenously with GXM, and the tissue distribution was determined. A macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 48 publications
6
56
0
1
Order By: Relevance
“…This suggests an essential role for macrophages in acquiring and storing GXM in various organs and is consistent with previous observations of GXM accumulation inside tissue macrophages in vivo (43,44). The mechanism responsible for enhanced GXM accumulation inside macrophages as opposed to monocytes is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests an essential role for macrophages in acquiring and storing GXM in various organs and is consistent with previous observations of GXM accumulation inside tissue macrophages in vivo (43,44). The mechanism responsible for enhanced GXM accumulation inside macrophages as opposed to monocytes is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies examined the in vivo distribution of capsular antigens (9,10,16,21). In perhaps the first such study, Kaplan (9) found similar results with glucuronoxylomannan, the major capsular polysaccharide from Cryptococcus neoformans.…”
Section: Discussionmentioning
confidence: 68%
“…All estimates of the amounts of ␥DPGA in tissues were corrected for ␥DPGA found in the plasma volume in each tissue (8). Estimates of serum ␥DPGA were calculated in a manner similar to that of Grinsell et al (10), assuming that the blood volume for a mouse is 5.77 ml/100g, that half of the blood volume is plasma, and that the average weight of each mouse is 20 g. A preliminary experiment was done in which tissues were spiked with purified ␥DPGA. A comparison of immunoassays using purified ␥DPGA alone and ␥DPGA in the presence of tissue homogenates showed no effect of the tissue homogenates on assay performance.…”
Section: Methodsmentioning
confidence: 99%
“…This prolonged action could be related to the fact that GXM remains internalized in macrophages for Ͼ1 mo (60). Hence, the two effects could be related and follow parallel pathways.…”
Section: Discussionmentioning
confidence: 99%